Assessing green gentrification in historically disenfranchised neighborhoods: a longitudinal and spatial analysis of Barcelona. Issue 3 (16th March 2018) - Anguelovski, Isabelle; Connolly, James J. T.; Masip, Laia; Pearsall, Hamil
ABSTRACT: To date, little is known about the extent to which the creation of municipal green spaces over an entire city addresses social or racial inequalities in the distribution of environmental amenities – or whether such an agenda creates contributes to green gentrification. In this study, we evaluate the effects of creating 18 green spaces in socially vulnerable neighborhoods of Barcelona during the 1990s and early 2000s. We examined the evolution over time of six socio-demographic gentrification indicators in the areas close to green spaces in comparison with the entire districts. Our results indicate that new parks in the old town and formerly industrialized neighborhoods seem to have experienced green gentrification. In contrast, most economically depressed areas and working-class neighborhoods with less desirable housing stock and more isolated from the city center gained vulnerable residents as they became greener, indicating a possible redistribution and greater concentration of vulnerable residents through the city.